Extensive testing and public health interventions for the control of covid-19 in the republic of cyprus between march and may 2020 - Quattrocchi, Annalisa; Mamais, Ioannis; Tsioutis, Constantinos; Christaki, Eirini; Constantinou, Costas L.; Koliou, Maria; Pana, Zoi Dorothea; Silvestros, Valentinos; Theophanous, Fani; Haralambous, Christos; Stylianou, Androulla; Sotiriou, Sotiroula; et al. (My University, 2020)
Coronavirus disease 2019 (COVID-19) has significantly affected the well-being of individuals worldwide. We herein describe the epidemiology of COVID-19 in the Republic of Cyprus during the first epidemic wave (9 March–3 May 2020). We analyzed surveillance data from laboratory-confirmed cases, including targeted testing and population screening. Statistical analyses included logistic regression. During the surveillance period, 64,136 tests (7322.3 per 100,000) were performed, 873 COVID-19 cases were diagnosed, and 20 deaths were reported (2.3%). Health-care workers (HCWs) represented 21.4% of cases. Overall, 19.1% of cases received hospital care and 3.7% required admission to Intensive Care Units. Male sex (adjusted Odds Ratio (aOR): 3.04; 95% Confidence Interval (CI): 1.97–4.69), increasing age (aOR: 1.56; 95%CI: 1.36–1.79), symptoms at diagnosis (aOR: 6.05; 95%CI: 3.18–11.50), and underlying health conditions (aOR: 2.08; 95%CI: 1.31–3.31) were associated with hospitalization. For recovered cases, the median time from first to last second negative test was 21 days. Overall, 119 primary cases reported 616 close contacts, yielding a pooled secondary attack rate of 12% (95%CI: 9.6–14.8%). Three population-based screening projects, and two projects targeting employees and HCWs, involving 25,496 people, revealed 60 positive individuals (0.2%). Early implementation of interventions with targeted and expanded testing facilitated prompt outbreak control on the island.
Keywords: andemic; COVID-19; Cyprus; Contact tracing; Containment measures; Surveillance